Effect of ritodrine tocolysis on fetal cardiac output distribution to the placenta - Ryuichi Shimaoka; Tomomi Shiga; Ken-ichirou Morishige (IMR Press, 2021)
Background: Adequate placental perfusion is important for fetal development and well-being, but the effect of tocolysis on placental perfusion is unclear. The aim of this study was to evaluate changes in fetal cardiac output distribution to the placenta following ritodrine tocolysis. Methods: This retrospective study involved 244 ultrasound findings in 142 singleton cases of appropriate for gestational age fetuses. The fetal cardiac output distribution to the placenta was defined and calculated as the percentage of umbilical vein flow volume (UVFV) based on the combined cardiac output (CCO). Ultrasound findings of 28 patients in the ritodrine group and 114 patients in the control group were compared using the unpaired t-test and Mann-Whitney U-test. Results: The CCO and UVFV increased as gestation progressed. On the other hand, distribution to the placenta was constant at approximately 15% from 28 to 35 weeks of gestation. Compared with the control group, the ritodrine group showed a significant increase in fetal heart rate, and the CCO also increased. The increase in UVFV in the ritodrine group was attributed to a significant increase in both the umbilical vessel diameter and blood flow velocity. As a result, distribution to the placenta in the ritodrine group was constant at about 20% and had a 5% increase at each week of gestation compared to the control group. Conclusions: To conclude, ritodrine tocolysis increased the fetal cardiac output distribution to the placenta. Additional research is required to determine whether tocolysis improves the placental perfusion in fetal growth restriction due to reduced placental perfusion.